A unified framework for business process intelligence - Sohail, A. (Springer Verlag, 2014)
Enterprises are striving to cut down their cost and the same time maintains an expectable level of quality in service delivery to keep the competitive edge. Integral to that is an analysis of business processes in order to identify inefficiencies in the design as well as execution of processes. Subsequently, based on the analysis improvement actions are taken. The techniques to identify inefficiencies in process are categorized into two types, a-priori (pre-execution) analysis and posterior (post-execution) analysis. This study focuses on posterior analysis, in which the data produced as a result of process execution are used to identify inefficiencies such as execution delay, and resource utilization. The aim of study is to analyze the existing work on business process improvement and build a unified framework for business process intelligence. Â© Springer Science+Business Media Singapore 2014.